Recent similarity in distribution ranges does not mean a similar postglacial history: a phylogeographical study of the boreal tree species Alnus incana based on microsatellite and chloroplast DNA variation. Issue 4 (1st February 2016) - Mandák, Bohumil; Havrdová, Alena; Krak, Karol; Hadincová, Věroslava; Vít, Petr; Zákravský, Petr; Douda, Jan
Summary: We reconstructed the historical pattern of postglacial biogeographic range expansion of the boreal tree species Alnus incana in Europe. To assess population genetic structure and diversity, we performed a combined analysis of nuclear microsatellite loci and chloroplast DNA sequences (65 populations, 1004 individuals). Analysis of haplotype and microsatellite diversity revealed that southeastern refugial populations situated in the Carpathians and the Balkan Peninsula did not spread north and cannot be considered as important source populations for postglacial recolonization of Europe; populations in Eastern Europe did not establish Fennoscandian populations; populations in Fennoscandia and Eastern Europe have no unique genetic cluster, but represent a mix with a predominant cluster typical for Central Europe; and that colonization of Fennoscandia and Eastern Europe took place from Central Europe. Our findings highlight the importance of an effective refugium in Central Europe located outside classical southern refugia confirming the existence of northern refugia for boreal trees in Europe. The postglacial range expansion of A. incana did not follow the model established for Picea abies . Fennoscandian populations are not derived from Eastern European ones, but from Central European ones.